Cardio-ankle Velocity Index (CAVI) as a Marker of Multivessel Coronary Artery Disease in Diabetic Patient - Talib, Ali Abdulkarim (International Journal of Psychosocial Rehabilitation, 2020)
Aim: To investigate the ability of the arterial stiffness parameter cardio-ankle velocity index (CAVI) to predict coronary disease in diabetic patient.Method: 155 consecutive patients underwent CAVI prior for coronary angiography for different indications between March 2018 until March 2019 at Al Hussein teaching hospital-Samawah city-Iraq. Patients with atrial fibrillation, aortic valve regurgitation and low Ankle Brachial Index (ABI